The Atonement : A Novel - Lewis, Beverly 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
"An Amish woman who has given up hope of marriage seeks to redeem the guilt from her past by volunteering her time in Lancaster County, and a young Englisher interested in the self-sufficiency of the Amish seeks mentorship from her father"--
Keywords: Amish -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Romance fiction